2015
DOI: 10.1179/1752628015y.0000000026
|View full text |Cite
|
Sign up to set email alerts
|

The Figure of the Soldier: Discourses of Indisputability and Heroism in a New Danish Commemorative Practice

Abstract: This article explores discourses on the Danish soldier in a new memory practice, a national Flag-Flying Day for Denmark's deployed Personnel (FFDDP), launched in 2009. Analysis of the official speeches on the FFDDP in 2013 shows that the figure of the soldier is placed in discourses linking humanitarianism, heroism, and ethics. What makes the Danish case particularly interesting is that the commemorative practice is so recent and that the discourses presented in this practice seem to already be mimicking inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…As observed by Hass, the body of the individual soldier frequently stands in for the body politic (1998). In instances of national triumph, the ‘soldier becomes a proponent for a society’s whole set of values’, an embodiment of virtue and heroism (Dahl Christensen, 2015: 355). Following collective shame or loss, the wounded body of the soldier – the veteran – comes to represent the trauma and failure of the nation (Sturken, 1997).…”
Section: The Soldier and The Universalized Legitimation Of Violencementioning
confidence: 99%
See 1 more Smart Citation
“…As observed by Hass, the body of the individual soldier frequently stands in for the body politic (1998). In instances of national triumph, the ‘soldier becomes a proponent for a society’s whole set of values’, an embodiment of virtue and heroism (Dahl Christensen, 2015: 355). Following collective shame or loss, the wounded body of the soldier – the veteran – comes to represent the trauma and failure of the nation (Sturken, 1997).…”
Section: The Soldier and The Universalized Legitimation Of Violencementioning
confidence: 99%
“…Critical analyses of war, the military and (usually Western) society frequently invoke key cultural figures to analytically identify, and succinctly convey, the ‘messy’ assemblages of discourse, materiality, semiotics and affect that legitimate state violence (Haraway, 1997: 8–12). Chief amongst these have been the figurative soldier – communicating idealized values of individual autonomy, masculinity and nationalist heroism (Dahl Christensen, 2015) – and the wounded veteran, suggesting themes of victimization, failure and, potentially, betrayal (Achter, 2010). Each of these figures conveys a series of metaphorical tropes (Haraway, 1997) that exceed their production within a particular time and place.…”
Section: Introductionmentioning
confidence: 99%
“…It has been noted that Denmark has seen a renewal of a patriotic discourse on sacrifice in which military heroism is vital to constructing nationhood (Marklund, 2013a; Refslund Sørensen, 2017). However, some researchers also stress that the contemporary narrative of the ‘return of the fallen’ includes references to the global context, democracy and human rights, whereas the masculinist, violent dimensions of heroic sacrifice are downplayed (Dahl Christensen, 2015; Marklund, 2013a).…”
Section: Military Heroism In Denmark and Swedenmentioning
confidence: 99%
“…Daniel Boorstin (1992 [1961]) and Orrin E Klapp (2014 [1962]) have contributed to bringing into focus the social dynamics of the hero phenomenon, while the Changing Character of War programme at Oxford University has stressed the social construction of heroes as ‘an ongoing process in which many actors participate, and in which the meaning of heroism is contested and constantly reinterpreted’ (Scheipers, 2014: 15). Despite evidence that the soldier hero has lost some glamour in the shadows of World War I and the war in Vietnam (Calder, 2004; Mosse, 1994), a growing body of literature has persuasively shown that military heroes remain familiar figures to the armed forces, the political debate, the media, and popular culture (Christensen, 2016; Dawson, 1994; Frühstück, 2007; Goren, 2007; Kelly, 2012; Papayanis, 2010; Scheipers, 2014; Woodward, 2000). These studies have examined heroification as a discourse within society, with special reference to the formation of nationhood and masculinities.…”
Section: The Study Of (Soldier) Heroesmentioning
confidence: 99%
“…Inspired by the USA and the UK, Denmark has developed a policy of honouring military personnel in the wake of the growing international engagement of the Danish Defence after the end of the Cold War. Denmark held its first National Flag Day for Danes Serving Abroad on 5 September 2009, a day that involved homecoming parades, the hoisting of flags, church services, and public speeches in front of the Parliament and in many provincial towns (Christensen, 2016; Reeh, 2011; Sørensen and Pedersen, 2012). As a spatial equivalent to the flag day, Parliament decided to build the Monument to Denmark’s International Effort since 1948, inaugurated by HM Queen Margrethe II in 2011, one year after the enactment of the first Danish veterans’ policy (Ministry of Defence of Denmark, 2010; Sørensen, 2016).…”
Section: Introductionmentioning
confidence: 99%